Automatic negative thoughts as contributing factors to adults with conversion disorder - Faiqa Tahir; Sadiq , Riffat (Journal of the Pakistan Medical Association, 2022)
Objectives: To see if automatic negative thoughts contributed to conversion disorder in adults. Method: The case-control study was conducted in Lahore and Faisalabad, Pakistan, from February 2017 to September 2019, and comprised adult patients of either gender diagnosed with conversion disorder at hospitals and private clinics in the two cities. Healthy adults without conversion disorder were recruited from the same cities. Data was collected using a semi-structured brief interview form and the Urdu version of the 30-item Automatic Thoughts Questionnaires (ATQ-30). Data was analysed using SPSS 22. Results: Of the 150 subjects, 75(50%) each were cases and controls. Overall, there were 54(36%) males and 96(64%) females. The cases reported more automatic negative thoughts than the controls (p<0.001). Besides, negative automatic thoughts related to helplessness and low self-esteem were reported by both the cases and the controls (p>0.05). Conclusion: Automatic negative thoughts contributed to the development of conversion disorder in adults. Key Words: Automatic negative thoughts, Conversion disorder, Maladjustment, Negative self-concept.